Proteomics analysis reveals differential acclimation of coastal and oceanic Synechococcus to climate warming and iron limitation - Schiksnis, Cara; Xu, Min; Saito, Mak A.; McIlvin, Matthew; Moran, Dawn; Bian, Xiaopeng; John, Seth G.; Zheng, Qiang; Yang, Nina; Fu, Feixue; Hutchins, David A. (Frontiers in Microbiology, 2024)
In many oceanic regions, anthropogenic warming will coincide with iron (Fe) limitation. Interactive effects between warming and Fe limitation on phytoplankton physiology and biochemical function are likely, as temperature and Fe availability affect many of the same essential cellular pathways. However, we lack a clear understanding of how globally significant phytoplankton such as the picocyanobacteria Synechococcus will respond to these co-occurring stressors, and what underlying molecular mechanisms will drive this response. Moreover, ecotype-specific adaptations can lead to nuanced differences in responses between strains. In this study, Synechococcus isolates YX04-1 (oceanic) and XM-24 (coastal) from the South China Sea were acclimated to Fe limitation at two temperatures, and their physiological and proteomic responses were compared. Both strains exhibited reduced growth due to warming and Fe limitation. However, coastal XM-24 maintained relatively higher growth rates in response to warming under replete Fe, while its growth was notably more compromised under Fe limitation at both temperatures compared with YX04-1. In response to concurrent heat and Fe stress, oceanic YX04-1 was better able to adjust its photosynthetic proteins and minimize the generation of reactive oxygen species while reducing proteome Fe demand. Its intricate proteomic response likely enabled oceanic YX04-1 to mitigate some of the negative impact of warming on its growth during Fe limitation. Our study highlights how ecologically-shaped adaptations in Synechococcus strains even from proximate oceanic regions can lead to differing physiological and proteomic responses to these climate stressors.